Compact of Free Association Migrants and Health Insurance Policies: Barriers and Solutions to Improve Health Equity - Pearl A. McElfish PhD; Rachel S. Purvis PhD; Sheldon Riklon MD; Seiji Yamada MD (SAGE Publishing, 2019)
This commentary outlines the health insurance disparities of Compact of Free Association (COFA) migrants living in the United States. Compact of Free Association migrants are citizens of the Republic of the Marshall Islands, the Federated States of Micronesia, and the Republic of Palau who can live, work, and study in the United States without a visa. Compact of Free Association migrants make up a significant proportion of the rapidly growing Pacific Islander population in the United States. This article describes the historical and current relationships between the United States and the Compact nations and examines national policy barriers constraining health insurance access for COFA migrants. In addition, the commentary describes the state-level health policies of Arkansas, Hawai'i, and Oregon, which are the states where the majority of COFA migrants reside. Finally, policy recommendations are provided to improve health equity for COFA migrants.